Association between Guillain-Barré Syndrome and Application of the Janssen Vaccine - Acendra, Armando Hongming Yee; Sampayo, Faruk Hernandez; Robles, Andrea Carolina Wilcox; Ariza, Mayra Alejandra Villalobos; León, Juan Sebastián Therán; Badillo, Laura Yibeth Esteban (Jour Med Resh and Health Sci, 2022)
This update was carried out in order to establish an association between the application of the jhanssen vaccine and the development of Guillan-Barré syndrome. Materials and methods: A detailed bibliographic search of information published since 2020 is carried out, in the databases Pubmed, Elsevier, Scielo, Update, Medline, national and international libraries. Results: the FDA who notified the detection of 100 possible cases of the syndrome among the 12.8 million people who have received the Janssen vaccine in the United States, that is, it affected 0.0007% of the total. Discussion: immune stimulation induced by vaccination could theoretically result in GBS through a variety of possible mechanisms. Conclusion: the inflammatory response that develops after a COVID-19 infection would have a negative effect on activated T cells, which in turn release pro-inflammatory cytokines, fix complement, damage Schwann cells and finally produce myelin dissolution and as a potential result we have the development of Guillian-Barre syndrome. Key words: JANSSEN vaccine, Guillain-Barré syndrome, covid-19, peripheral nerves.